Rekonstruksi Kompetensi Guru: Dialektika Kuadran Glickman dan Kesadaran Epistemologis Perspektif Imam al-Ghazali - Najwa Hafana; Ahmad Barizi (Lembaga Yasin AlSys, 2026)
Although teacher competence has been widely studied in technical and pedagogical dimensions, studies that integratively reconstruct teacher competence through the dialectic of Glickman’s quadrant and epistemological awareness from the perspective of Imam Al-Ghazali remain limited. This study aims to analyze the reconstruction of teacher competence by integrating Carl D. Glickman’s developmental supervision theory and Imam Al-Ghazali’s typology of epistemological awareness. This study used a qualitative approach with library research, with the main data sources consisting of Carl D. Glickman’s works on developmental supervision and Imam Al-Ghazali’s Ihya’ ‘Ulum al-Din. The results showed that Glickman’s theory produces four teacher typologies, namely drop-out, unfocused worker, analytical observer, and professional, each of which requires different supervisory interventions. Meanwhile, Imam Al-Ghazali’s typology of epistemological awareness, namely Al-ʿAlim, An-Na’im, Al-Mustarsyid, and Al-Jahil, represents teachers’ level of awareness of the knowledge they possess. The dialectic between these two perspectives produces the concept of teachers’ epistemological competence, which includes reflective and analytical capacity, professional commitment, epistemic self-awareness, and moral-spiritual orientation. The conclusion of this study affirms that the development of teacher competence cannot rely solely on technical-pedagogical aspects but also needs to be supported by epistemological and moral-spiritual awareness. This reconstruction provides a theoretical contribution to the development of a more holistic and integrative paradigm of teacher professionalism between modern intellectual traditions and Islamic epistemology.